NAVIGATING DIGITAL DIALOGUE: ASNAF STUDENTS’ EXPERIENCES OF COMMUNICATION WITH TEACHERS IN HIGH POWER DISTANCE CONTEXTS - Haris, Mohd Izwan Izhar; Abu Bakar, Hanif Suhairi; Bahrudin, Asraful Anam (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
In Malaysian schools, high power distance often shapes communication between students and teachers. This phenomenological study explores how this dynamic affects asnaf students, a financially disadvantaged group, through qualitative interviews with 10 students aged 13 to 17 in a Perlis boarding school. The study examines three objectives: (a) the nature of two-way communication, (b) the channels through which it occurs, and (c) how channel characteristics affect communication quality. The findings revealed a central theme based on the three objectives: Hierarchical Communication Culture, with subthemes: Reluctance to Initiate, Dependence on Indirect Channels, and Digital Spaces as Safe Zones. Communication was often unidirectional in face-to-face settings, but mediated more freely through digital tools. These results emphasize the role of communication tools in overcoming cultural communication barriers. The study offers practical implications for educators to design communication systems that are sensitive to power dynamics and cultural expectations.